Implementation of the Green Port Concept in PT. Terminal Petikemas Surabaya - Dirmansyah, Denny; Setiono, Benny Agus; Nasihah, Ainun (Universitas Hang Tuah, 2024)
This research aims to implement the Green Port concept at PT Terminal Petikemas Surabaya. This research method uses descriptive qualitative methods including interviews, notes, field notes, pictures, and video recordings. The data collection technique used direct observation of the green port process at PT Terminal Petikemas Surabaya, interviews with operational staff, engineers, and field workers at PT Terminal Petikemas Surabaya, and documentation. The results of this study are a). The implementation of the green port concept at PT Terminal Peti Kemas Surabaya succeeded in improving environmental quality and operational efficiency, reducing carbon emissions and costs. These efforts reflect TPS commitment to sustainability, creating a competitive green port, and providing long-term benefits to the environment, economy and surrounding communities. b). Efforts to support the green port concept and improve sustainability include the use of renewable energy, energy use optimization, waste management, environmentally friendly transportation, education and training, and regular environmental monitoring. These efforts demonstrate the terminal's commitment to reducing environmental impacts and improving operational efficiency. c). The implementation of the green port concept at Surabaya Container Terminal has reduced emissions and carbon footprint, increased energy efficiency, managed waste well, and improved air and water quality. Equipment modernization and operational automation have also increased productivity and reduced waiting time. These positive impacts not only support environmental and operational sustainability, but also enhance the port's reputation and the quality of life of the surrounding community.